PERSPEKTIF HUKUM EKONOMI ISLAM TERHADAP PENGELOLAAN RETRIBUSI JALAN ATAS JASA PENGANGKUTAN PASIR - malik, mohsyahril; syaiin (Irtifaq, 2021)
The management of road fees for sand transportation services is often a polemic in the community. Meanwhile, the existence of an Islamic economic system implemented in the community has been able to minimize poverty and become an alternative in managing village funds. So with the perspective of Islamic economic law on the management of road levy funds that have been collected by the village government will be channeled to the development and benefit of the village. There will be no manipulation in terms of road retribution funds, as long as the government and the community support each other by applying Islamic economic principles. The effectiveness of the management of road retribution funds resulting from sand transportation services in Hadiluwih village should be able to make the community aware of the public good. Every activity that is oriented towards the safety of the world and the hereafter will demand and lead to the truth in accordance with Islamic teachings. This study aims to determine the management of road retribution funds in Hadiluwih village. To answer this problem, the researcher used a qualitative approach with the type of field research (field research) in which the data was taken directly from the source. In qualitative research, the researcher was confronted directly with the respondents, namely the Hadiluwih village administrators and the sand transportation service business actors. The Hadiluwih Village Government uses the theory of retribution, where the collection is carried out from individuals and agencies that pass through the village road because it will take the sand that is in Hadiluwih Village, so the village government makes regulations governing the collection, namely Hadiluwih Village Regulation Number 05 of 2018 concerning Retribution, In general, the purpose of the role of the government is to create benefits for the entire community, in the perspective of past economic law, namely maintaining benefit by means of min haytsu al-wujud and min haytsu al-adam. Keyword: Islamic Economic Law, Village Income, Road Retribution